Oxidation of DNA bases is influenced by their position in the DNA strand - Toh, Rou Jun (2013)
Electrochemical detection of DNA is an important field of research, with strong implications for next generation diagnostics. In this paper, we show that the electrochemical responses of DNA bases (guanine, adenine, thymine, cytosine) in terms of peak potentials and peak current may be influenced by the sequences of an oligomer at standard glassy carbon (GC), as well as electrochemically reduced graphene oxide electrode. We have observed that the effects were more significant on the oxidative peaks of adenine and thymine on the GC-electrode. Deviations in peak potentials were generally low. Our findings are principally important for fundamental studies and future developments in DNA detection and analysis.